Electron transport layer and preparation method thereof, solar cell and photovoltaic module

By using a mixture of transition metal sulfides and C60 in a mass ratio of 10:1 to 1:10 in perovskite solar cells, a highly stable van der Waals heterostructure is formed, which solves the problems of low stability of the C60 electron transport layer and low carrier mobility, thereby improving the photoelectric conversion efficiency of the solar cells.

CN121013564APending Publication Date: 2025-11-25TONGWEI SOLAR ENERGY (CHENGDU) CO LID
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411338872.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2025-11-25

AI Technical Summary

Technical Problem

In existing perovskite solar cells, when C60 is used as the electron transport layer, its low carrier mobility and poor stability hinder the improvement of photoelectric conversion efficiency.

Method used

A van der Waals heterostructure is formed by using a mixture of transition metal sulfides and C60 in a mass ratio of 10:1 to 1:10. The transition metal sulfides are stacked two-dimensional layered structures with C60 distributed in the edge region. The mixture is mixed by ball milling or ultrasonication to form a highly stable electron transport layer.

Benefits of technology

This improves the energy level matching between the electron transport layer and the perovskite layer, promotes carrier extraction and migration, reduces interface energy loss, enhances the stability of the electron transport layer and the carrier migration capability, and improves the photoelectric conversion efficiency of solar cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121013564A_ABST
    Figure CN121013564A_ABST
Patent Text Reader

Abstract

The invention relates to the field of solar cells, and discloses an electron transport layer and a preparation method thereof, a solar cell and a photovoltaic module, the electron transport layer is used for a perovskite solar cell and comprises transition metal sulfide and C60 in a mass ratio of (10: 1)-(1: 10), and a mixture of part or all of the transition metal sulfide and the C60 is of a Van der Waals heterostructure, the transition metal sulfide is of a stacked two-dimensional layered structure, the electron transport layer has high stability and carrier transport rate, and the stability and photoelectric conversion performance of the solar cell can be effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of solar cells, in particular to an electron transport layer, a preparation method thereof, a solar cell and a photovoltaic module. BACKGROUND

[0002] As an important component of perovskite solar cells, the electron transport layer plays a key role in extracting and transporting photo-generated electrons, blocking holes and modifying interfaces. However, the electron transport layer made of C 60 has low carrier mobility and poor stability, which hinders the improvement of the photoelectric conversion efficiency of perovskite solar cells. SUMMARY

[0003] The present application discloses an electron transport layer, a preparation method thereof, a solar cell and a photovoltaic module. The electron transport layer has high stability and high carrier transport rate, so that the solar cell has high stability and photoelectric conversion performance.

[0004] In a first aspect, the present application discloses an electron transport layer for perovskite solar cells, which comprises transition metal sulfide and C 60 in a mass ratio of 10:1 to 1:10, and a mixture of part or all of the transition metal sulfide and the C 60 is a van der Waals heterostructure, wherein the transition metal sulfide is a stacked two-dimensional layered structure.

[0005] Further, in the electron transport layer, the edge region of any one of the two-dimensional layered structures is distributed with the C 60 .

[0006] Further, the particle size of the C 60 is 0.5nm to 0.9nm, and the spacing between adjacent two of the two-dimensional layered structures is 0.0276nm to 0.3676nm.

[0007] Further, in the electron transport layer, the size of the transition metal sulfide is 40nm to 100nm; and / or,

[0008] In the electron transport layer, the thickness of the transition metal sulfide is 3nm to 27nm.

[0009] Further, the band gap of the electron transport layer is 1.2eV to 1.9eV.

[0010] Further, the transition metal sulfide comprises at least one of molybdenum disulfide, tungsten disulfide and titanium disulfide; and / or,

[0011] The thickness of the electron transport layer is 10-30 nm.

[0012] In a second aspect, the application discloses a preparation method of the electron transport layer of the first aspect, and the preparation method comprises the following steps:

[0013] The C 60 The electron transport layer is prepared after the C

[0014] Further, the C 60 The mixing method of the C

[0015] The C 60 The mixing time of the C

[0016] In a third aspect, the application discloses a solar cell, which comprises a substrate, a first transport layer, a perovskite layer and a second transport layer arranged on the substrate in sequence, one of the first transport layer and the second transport layer is the electron transport layer of any one of the first aspect, and the other is a hole transport layer.

[0017] Further, the substrate comprises a bottom cell and an electron-hole recombination layer arranged on the bottom cell, and the first transport layer is arranged on a side of the electron-hole recombination layer away from the bottom cell.

[0018] The solar cell further comprises a transparent conductive layer arranged on a side of the second transport layer away from the perovskite layer, and the solar cell further comprises a first electrode and a second electrode, the first electrode is arranged on a side of the transparent conductive layer away from the perovskite layer, and the second electrode is arranged on a side of the bottom cell away from the electron-hole recombination layer, one of the first electrode and the second electrode is a positive electrode, and the other is a negative electrode.

[0019] Alternatively, the substrate is a transparent conductive substrate, and the first transport layer is arranged on the transparent conductive substrate.

[0020] The solar cell further comprises a first electrode and a second electrode, the first electrode is arranged on a side of the second transport layer away from the perovskite layer, and the second electrode is arranged on a side of the transparent conductive substrate away from the first transport layer, one of the first electrode and the second electrode is a positive electrode, and the other is a negative electrode.

[0021] In a fourth aspect, the application discloses a photovoltaic module, which comprises the electron transport layer of any one of the first aspect or the solar cell of any one of the third aspect.

[0022] Compared with the prior art, the application has the beneficial effects that:

[0023] The electronic transport layer provided by the embodiments of the application comprises C 60 and the mass ratio of the transition metal sulfide, and the mass ratio is controlled within the above range, which can effectively improve the energy band of the electronic transport layer, so that the electronic transport layer has a higher matching degree with the perovskite layer, which is conducive to promoting the extraction and migration of interface charges and reducing the interface energy loss.

[0024] In addition, by controlling the mass ratio, the chemical environment of the electronic transport layer is adjusted, which is more conducive to the dissociation of the transition metal sulfide, which promotes the combination of C 60 and the transition metal sulfide, thereby forming a high-stable van der Waals heterostructure. Due to the non-covalent intermolecular interaction existing in the van der Waals heterostructure, C 60 and the transition metal sulfide have a higher interaction force, and the connection stability is higher, which is conducive to improving the stability of the electronic transport layer. Moreover, C 60 will also promote the transition metal sulfide to form more active sites, avoid the recombination of electrons and holes, and improve the migration ability of the carriers. In addition, due to the strong electron receiving ability of C 60 , the van der Waals heterostructure makes the transition metal sulfide and C 60 exist charge transfer, which is conducive to changing the energy band structure and the position of the Fermi level of the electronic transport layer, thereby being conducive to improving the electrical stability of the electronic transport layer and the photoelectric conversion efficiency of the solar cell.

[0025] In summary, by controlling the mass ratio of C 60 and the transition metal sulfide, not only the adaptability between the electronic transport layer and the perovskite layer is improved, but also a high-stable van der Waals heterostructure is formed, which can effectively improve the stability of the electronic transport layer, promote the transmission of the carriers, so that the solar cell has higher stability and photoelectric conversion performance. BRIEF DESCRIPTION OF DRAWINGS

[0026] In order to more clearly illustrate the technical solutions in the embodiments of the application, the drawings used in the embodiments will be briefly introduced. Obviously, the drawings in the following description are only some embodiments of the application, and for those skilled in the art, other drawings can also be obtained without creative labor.

[0027] Figure 1 is a structural schematic diagram of molybdenum disulfide provided by the embodiments of the application;

[0028] Figure 2is a schematic diagram of a horizontal plane of molybdenum disulfide provided by an embodiment of the present application 60 is a schematic diagram of distribution on molybdenum disulfide

[0029] Figure 3 is a schematic diagram of a horizontal plane of molybdenum disulfide provided by an embodiment of the present application

[0030] Figure 4 is a schematic diagram of a horizontal plane of molybdenum disulfide provided by an embodiment of the present application 60 is a schematic diagram of a horizontal plane of molybdenum disulfide provided by an embodiment of the present application

[0031] Figure 5 is a schematic diagram of a horizontal plane of molybdenum disulfide provided by an embodiment of the present application

[0032] Figure: 1, substrate; 11, bottom cell; 12, electron hole recombination layer; 2, first transport layer; 3, perovskite layer; 4, second transport layer; 5, transparent conductive layer; 61, first electrode; 62, second electrode; 7, passivation layer; 8, buffer layer; 9, antireflection layer. DETAILED DESCRIPTION

[0033] The technical solutions in the embodiments of the present application will be clearly and completely described below with reference to the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those of ordinary skill in the art without creative labor fall within the scope of protection of the present application.

[0034] In the present application, the orientations or positional relationships indicated by the terms "upper", "lower", "left", "right", "front", "back", "top", "bottom", "inner", "outer", "middle", "vertical", "horizontal", "lateral", "longitudinal", and the like are based on the orientations or positional relationships shown in the drawings. These terms are mainly used for better description of the present application and its embodiments, and are not used to limit the indicated devices, elements or components to have a specific orientation, or to be constructed and operated in a specific orientation.

[0035] In addition, in addition to being used to indicate orientations or positional relationships, the above-mentioned partial terms can also be used to indicate other meanings, for example, the term "upper" can also be used to indicate a certain dependent relationship or connection relationship in some cases. Those of ordinary skill in the art can understand the specific meanings of these terms in the present application according to the specific circumstances.

[0036] In addition, the terms "first", "second", and the like are mainly used to distinguish different devices, elements or components (the specific types and structures can be the same or different), and are not used to indicate or imply the relative importance and quantity of the indicated devices, elements or components. Unless otherwise specified, the meaning of "multiple" is two or more.

[0037] The technical solutions provided by the present application will be further described below in combination with embodiments and drawings.

[0038] In order to transport the carrier electrons generated by the perovskite layer after absorbing sunlight to the electrode, an important film layer structure, the electron transport layer, needs to be set. The electron transport layer, as an important part of the solar cell, plays a key role in extracting and transporting photo-generated electrons, blocking holes, modifying interfaces, and reducing charge recombination, and the material selection of the electron transport layer also affects the transport effect of the electron transport layer on electrons.

[0039] Specifically, taking C 60 as an example, due to its highly conjugated molecular structure, high electron accepting property, three-dimensional electron transport characteristics, relatively rich source, and low price, it has been widely used as an electron transport layer. However, when C 60 is used as an electron transport layer material, due to its low energy level, the matching degree with the energy level of the perovskite layer is poor, so that the carrier is prone to recombination, thereby affecting the migration ability of the carrier of the electron transport layer. In addition, long-term light irradiation causes C 60 to easily degrade and expand, thereby affecting the stability of the electron transport layer.

[0040] Based on the above problems, the embodiments of the present application provide an electron transport layer and a preparation method thereof, a solar cell and a preparation process thereof, and a photovoltaic module, to solve the problems of poor stability and blocked carrier transport of C 60 as an electron transport layer, thereby improving the performance of the solar cell.

[0041] In a first aspect, the embodiments of the present application disclose an electron transport layer for a perovskite solar cell, the electron transport layer comprising a transition metal sulfide and C 60 in a mass ratio of 10:1 to 1:10, and a mixture of part or all of the transition metal sulfide and C 60 being a van der Waals heterostructure, wherein the transition metal sulfide is a stacked two-dimensional layered structure.

[0042] The electron transport layer in the embodiments of the present application comprises C 60 and a transition metal sulfide, wherein, since the mass ratio of C 60 and the transition metal sulfide is 10:1 to 1:10, the band gap of the electron transport layer has a high matching degree with the perovskite layer, which helps to inhibit the recombination of the carrier in the electron transport layer, promote the extraction and migration of the interface charge, and reduce the interface energy loss.

[0043] In addition, within the range of the mass ratio, it is helpful to regulate the chemical environment of the electron transport layer, so that it is more conducive to the dissociation of the transition metal sulfide and promotes C60 and transition metal sulfides, thereby helping to form a high-stability van der Waals (vdW) heterostructure. And because the C 60 has a higher interaction force with the transition metal sulfides, the connection is more stable, avoiding the agglomeration of C 60 , and improving the stability of the electron transport layer. Moreover, the C 60 also promotes the transition metal sulfides to form more active sites, inhibits the recombination of electrons and holes, and improves the migration ability of the carriers. In addition, because of the strong electron receiving ability of C 60 , the vdW heterostructure causes there to be a charge transfer between the transition metal sulfides and C 60 , which helps to change the energy band structure and the position of the Fermi level of the electron transport layer, thereby improving the electrical stability of the electron transport layer and improving the photoelectric conversion efficiency of the solar cell.

[0044] In summary, the electronic transport layer provided in the present application, by controlling the mass ratio of the transition metal sulfides and C 60 in the electronic transport layer, not only helps to improve the energy level adaptation of the electronic transport layer and the perovskite layer, but also helps to form a high-stability vdW heterostructure, thereby helping to improve the transmission efficiency of the carriers and improve the stability of the electronic transport layer.

[0045] Among them, the mixture of part of the transition metal sulfides and C 60 means that the existence form of the transition metal sulfides and C 60 in the electronic transport layer includes not only the vdW heterostructure, but also free transition metal sulfides, free C 60 ; the mixture of all transition metal sulfides and C 60 means that the existence form of the transition metal sulfides and C 60 in the electronic transport layer only includes the vdW heterostructure.

[0046] And, as shown in Figure 1 , taking molybdenum disulfide as an example, the monolayer structure in the molybdenum disulfide is that two layers of sulfur atoms sandwich one layer of molybdenum atoms, forming a structure similar to a sandwich (S-Mo-S). After stacking several layers of S-Mo-S structures, a stacked two-dimensional layered structure is formed.

[0047] Further, in the electronic transport layer, the edge region of any two-dimensional structure is distributed with C 60 .

[0048] The edge region refers to the outermost boundary of the two-dimensional structure. The atoms in the edge region have a higher unsaturation and more dangling bonds, and are easy to produce more active sites. As shown in Figure 2 ,Figure 2 C in the transition metal sulfide 60 C in the transition metal sulfide 60 The number of active sites in the edge region of the transition metal sulfide can be further increased, so that the transition metal sulfide has a high electron transfer rate with C 60 , which is beneficial to the separation of electron-hole pairs and further inhibits the recombination of carriers, thereby improving the electron transport capacity.

[0049] Further, the particle size of C 60 is 0.5 nm to 0.9 nm, and the spacing between adjacent two-dimensional layered structures is 0.0276 nm to 0.3676 nm.

[0050] Since the particle size of C 60 is greater than the spacing between adjacent two-dimensional layered structures, it indicates that the particle size of C 60 is large, and the spacing between adjacent two-dimensional layered structures is small, so C 60 is mainly distributed in the edge region of the transition metal sulfide, which can effectively increase the number of active sites in the edge region of the transition metal sulfide, thereby further improving the electron transfer capacity.

[0051] Since C 60 is a spherical structure or a spherical-like structure, C 60 is a circular structure or a circular-like structure in the horizontal plane projection, so the particle size refers to the diameter of the shape of C 60 in the horizontal plane projection.

[0052] Further, in the electron transport layer, the size of the transition metal sulfide is 40 nm to 100 nm.

[0053] Since the size of the transition metal sulfide is small, the specific surface area is high, which is beneficial to generate more active sites and promote the formation of more van der Waals heterostructures, thereby effectively improving the transport capacity of carriers.

[0054] Also, the size of the transition metal sulfide and the particle size of C 60 can be analyzed and measured by a scanning electron microscope, and can also be measured by other preparation methods, as long as the size of the transition metal sulfide and the particle size of C 60 can be measured, which is not limited here.

[0055] The size of the transition metal sulfide refers to the longest side length of the horizontal plane projection structure of the two-dimensional layered structure. For example, as shown in Figure 3 , when the horizontal plane projection of any one layer of two-dimensional structure is a parallelogram structure, the size refers to the maximum side length of the parallelogram.

[0056] Furthermore, in the electron transport layer, the thickness of the transition metal sulfide is 3 nm to 27 nm. When the thickness of the transition metal sulfide is within the above range, it can effectively reduce the interface scattering of charge carriers and reduce the defects in the electron transport layer, thereby helping to further improve the carrier transport effect.

[0057] When the band gap of the electron transport layer is 1.2 eV to 1.9 eV, its band gap matches that of the perovskite layer more smoothly, allowing electrons to transfer more smoothly from the perovskite layer to the electron transport layer. This reduces energy loss and the probability of electron recombination at the interface, thereby helping to further improve the carrier transport rate and the photoelectric conversion efficiency of the solar cell.

[0058] Furthermore, the transition metal sulfides include at least one of molybdenum disulfide, tungsten disulfide, and titanium disulfide. When used as electron transport layer materials, these materials all exhibit good corrosion resistance and thermodynamic stability, thus contributing to the stability of the electron transport layer and improving the lifespan of the solar cell.

[0059] Furthermore, the thickness of the electron transport layer is 10 nm to 30 nm. When the thickness of the electron transport layer is within this range, the coverage of the perovskite layer is high, which can effectively block the transport of holes to electrons, improve light transmittance, increase the transport rate of charge carriers, and reduce defects in the electron transport layer, thus helping to reduce the probability of electron-hole recombination and improve the fill factor and series resistance of the battery. For example, the thickness of the electron transport layer is 10 nm, 14 nm, 18 nm, 20 nm, 25 nm, and 30 nm.

[0060] Secondly, embodiments of this application disclose a method for preparing an electron transport layer as described in the first aspect, the method comprising the following steps:

[0061] First, C 60 After being mixed with transition metal sulfides at a mass ratio of 10:1 to 1:10, an electron transport layer is prepared.

[0062] like Figure 4 As shown, due to C 60 With a lattice constant close to that of transition metal sulfides, it exhibits high lattice matching, which facilitates the generation of mutual forces between the two materials, connecting them through van der Waals forces. Furthermore, both materials are chemically stable and do not react upon contact, thus forming a highly stable van der Waals heterostructure. Among them, C... 60 The degree of mixing with transition metal sulfides can affect the content of van der Waals heterojunctions formed; the more uniform the mixing, the higher the C content. 60The higher the probability of contact with the transition metal sulfide, the higher the content of van der Waals heterostructure formed.

[0063] C 60 The mixing method of the transition metal sulfide includes ball milling or ultrasonic method. By using the above-mentioned physical and mechanical mixing method, the solubility of the two materials does not need to be considered, the difficulty of preparation is reduced, the processing efficiency is improved, and the multi-layer structure in the transition metal sulfide is also dissociated into a single-layer two-dimensional structure, forming smaller transition metal sulfides and generating more active sites. When the ball milling method is used, the mechanical force in the ball milling process helps to dissociate the transition metal sulfide into smaller sizes, and the transition metal sulfide is in contact with the C 60 The transition metal sulfide directly interacts and stacks with each other, thereby forming a specific layered stacked heterostructure.

[0064] In addition, the speed of ball milling is controlled to be 500 r / min-2500 r / min. Within this range, the grinding is sufficient, the C 60 The area of mutual contact with the transition metal sulfide helps to form the van der Waals heterostructure, and also helps to avoid material overheating caused by high friction, avoid adverse effects on the structure, and improve the performance of the electron transport layer.

[0065] Further, the C 60 The mixing time of the transition metal sulfide is 12 h-16 h. When the mixing time is controlled within the above range, the uniformity of mixing is improved, the dissociation of the transition metal sulfide is further promoted, the size of the transition metal sulfide is smaller, and the van der Waals heterostructure is formed.

[0066] In a third aspect, the embodiments of the present application disclose a solar cell, which comprises a substrate, and a first transport layer, a perovskite layer and a second transport layer arranged on the substrate in sequence. One of the first transport layer and the second transport layer is the electron transport layer of the first aspect, and the other is a hole transport layer.

[0067] The perovskite layer of the present application can be prepared by the following preparation method, or can be prepared by other preparation methods. As long as the perovskite layer of the present application can be prepared, the preparation process of the perovskite layer is not limited in the present application.

[0068] Specifically, the preparation process of the perovskite layer includes:

[0069] The lead skeleton layer is prepared by multi-source co-evaporation on the first transport layer; then the cation solution is spin-coated on the lead skeleton layer, and the perovskite layer is obtained after annealing. The evaporation source material of the lead skeleton layer includes PbI2 and CsX, and the evaporation rate ratio of PbI2 and CsX is 13:1-15:1. The cation solution is obtained by dissolving FAI, FABr, MABr and MACl in ethanol or isopropanol, and is spin-coated on the lead skeleton layer by using a slot coating method or a doctor blade coating method. After annealing, the perovskite layer is prepared. And CsX can improve the porosity and the loose degree of the structure of the lead skeleton layer, so that the cation solution can enter the inside of the lead skeleton layer and react with it, thereby improving the crystalline quality of the perovskite layer. When the evaporation rate ratio of PbI2 and CsX is 13:1-15:1, the structural stability of the lead skeleton layer is ensured and it has a suitable pore structure; neither will the lead skeleton layer have too many pores due to too low rate, nor will the amount of CsX acting on the lead skeleton layer be limited due to too high rate, thereby leading to too few pores of the lead skeleton layer, which is not conducive to the subsequent diffusion of cations into the inside of the skeleton layer. Wherein, X includes at least one of Br and Cl. In addition, the thickness of the lead skeleton layer is controlled to be 300-500 nm, so that it has good matching with the band gap of the electron transport layer, thereby further reducing the interface recombination and improving the transport efficiency of the carriers.

[0070] Exemplarily, the evaporation rate ratio is 13:1, 14:1, 15:1, etc. And CsX includes at least one of CsBr and CsCl.

[0071] In the preparation process, the perovskite layer is prepared by using a two-step method, in which the lead skeleton layer is first prepared and then the cation solution is spin-coated. The cation solution undergoes self-assembly reaction through the lead skeleton layer to convert the lead skeleton layer into perovskite phase, so that the perovskite layer prepared has high coverage on the substrate and complete morphology, and can keep consistent with the structure of the substrate. If a substrate with a textured structure is used, the perovskite layer prepared has a textured structure, so that the light trapping property of the substrate textured structure can be utilized to improve the short-circuit current density of the solar cell, thereby improving the photoelectric conversion rate of the perovskite solar cell.

[0072] The hole transport layer includes a nickel oxide layer arranged close to the substrate and a carbazole organic small molecule layer containing phosphonic acid groups arranged on the nickel oxide layer away from the substrate. The carbazole organic small molecule layer containing phosphonic acid groups regulates the hydrophilic and hydrophobic properties of the surface of the nickel oxide layer, increases the crystal quality of the perovskite layer, improves the carrier lifetime, and significantly optimizes the surface work function of the nickel oxide, so that the interface between the hole transport layer and the perovskite layer has high matching degree, thereby improving the interface transport properties of the carrier. In addition, when the first electron transport layer is the hole transport layer, the carbazole organic small molecule layer containing phosphonic acid groups can also act as a barrier layer to prevent the high-valence metal elements in the hole transport layer from oxidizing the perovskite layer and reduce the structural damage of the perovskite layer.

[0073] It can be understood that the material of the carbazole organic small molecule layer containing phosphonic acid groups includes at least one of 2-PACZ (2-(9H-carbazol-9-yl)ethyl) phosphonic acid, 4-PACZ (4-(9H-carbazol-9-yl)ethyl) phosphonic acid, and Me-2PACZ (2-(3,6-Dimethyl-9H-carbazol-9-yl)ethyl] phosphonic acid).

[0074] In an alternative embodiment, the solar cell is a perovskite crystalline silicon laminated solar cell. As shown in FIG. 1, the substrate 1 includes a bottom cell 11 and an electron-hole recombination layer 12 arranged on the bottom cell 11, and the first transport layer 2 is arranged on the side of the electron-hole recombination layer 12 away from the bottom cell 11. Figure 5 The first transport layer 2 includes a nickel oxide layer 21 arranged close to the substrate 1 and a carbazole organic small molecule layer 22 containing phosphonic acid groups arranged on the nickel oxide layer 21 away from the substrate 1.

[0075] The solar cell further includes a transparent conductive layer 5 arranged on the side of the second transport layer 4 away from the perovskite layer 3, and the solar cell further includes a first electrode 61 and a second electrode 62. The first electrode 61 is arranged on the side of the transparent conductive layer 5 away from the perovskite layer 3, and the second electrode 62 is arranged on the side of the bottom cell 11 away from the electron-hole recombination layer 12. One of the first electrode 61 and the second electrode 62 is a positive electrode, and the other is a negative electrode.

[0076] Further, the solar cell further comprises a passivation layer 7 arranged between the perovskite layer 3 and the second transport layer 4, the material of the passivation layer 7 comprises lithium fluoride, and the thickness of the passivation layer 7 is 0.5 nm to 1 nm. The passivation layer 7 can passivate the interface defects of the perovskite layer 3, improve the matching degree of the perovskite layer 3 and the second transport layer 4, reduce the interface defects, and reduce the interface recombination, thereby improving the extraction of the carriers by the second transport layer 4 and improving the migration ability of the carriers. The thickness of the passivation layer 7 is set in the above range to avoid that the passivation layer 7 is too thin to repair the interface defects of the perovskite layer 3 and too thick to affect the transmission of the carriers. For example, the thickness of the passivation layer is 0.5 nm, 0.7 nm, 0.9 nm, 1 nm, or the like.

[0077] Further, the solar cell further comprises a passivation layer 7 arranged between the perovskite layer 3 and the second transport layer 4, the material of the passivation layer 7 comprises lithium fluoride, and the thickness of the passivation layer 7 is 0.5 nm to 1 nm. The passivation layer 7 can passivate the interface defects of the perovskite layer 3, improve the matching degree of the perovskite layer 3 and the second transport layer 4, reduce the interface defects, and reduce the interface recombination, thereby improving the extraction of the carriers by the second transport layer 4 and improving the migration ability of the carriers. The thickness of the passivation layer 7 is set in the above range to avoid that the passivation layer 7 is too thin to repair the interface defects of the perovskite layer 3 and too thick to affect the transmission of the carriers. For example, the thickness of the passivation layer is 0.5 nm, 0.7 nm, 0.9 nm, 1 nm, or the like.

[0078] Further, the solar cell further comprises a passivation layer 7 arranged between the perovskite layer 3 and the second transport layer 4, the material of the passivation layer 7 comprises lithium fluoride, and the thickness of the passivation layer 7 is 0.5 nm to 1 nm. The passivation layer 7 can passivate the interface defects of the perovskite layer 3, improve the matching degree of the perovskite layer 3 and the second transport layer 4, reduce the interface defects, and reduce the interface recombination, thereby improving the extraction of the carriers by the second transport layer 4 and improving the migration ability of the carriers. The thickness of the passivation layer 7 is set in the above range to avoid that the passivation layer 7 is too thin to repair the interface defects of the perovskite layer 3 and too thick to affect the transmission of the carriers. For example, the thickness of the passivation layer is 0.5 nm, 0.7 nm, 0.9 nm, 1 nm, or the like.

[0079] It should be noted that the preparation method of the passivation layer, the buffer layer, the transparent conductive layer, the anti-reflection layer, the first electrode, and the second electrode comprises one or more of metal evaporation, atomic layer vapor deposition, and magnetron sputtering. The present application does not make specific limitations in this regard.

[0080] In another alternative embodiment, the solar cell is a perovskite single-junction solar cell. The substrate is a transparent conductive substrate, and the first transport layer is arranged on the transparent conductive substrate.

[0081] The solar cell further comprises a first electrode and a second electrode, the first electrode is arranged on the side of the second transport layer away from the perovskite layer, and the second electrode is arranged on the side of the transparent conductive substrate away from the first transport layer, one of the first electrode and the second electrode is a positive electrode, and the other is a negative electrode.

[0082] In a fourth aspect, the embodiments of the present application disclose a photovoltaic module, which comprises the electron transport layer of the first aspect or the solar cell of the third aspect.

[0083] The technical solutions of the present application will be further explained in combination with more specific embodiments and experimental test results.

[0084] Embodiment one:

[0085] The present application provides a kind of solar cell, the solar cell is laminated solar cell, the preparation method of the solar cell includes the following steps:

[0086] Providing substrate: providing HJT crystalline silicon bottom cell, electron transport composite layer is prepared in the light receiving surface of the bottom cell by magnetron sputtering in sequence;

[0087] Forming hole transport layer on substrate: 20nm thick nickel oxide hole transport layer is deposited by physical vapor deposition method, 2-PACz hole transport layer is prepared by thermal evaporation method;

[0088] Forming perovskite layer, electron transport layer in sequence on first transport layer:

[0089] Multi-source co-evaporation is made to produce lead skeleton layer on hole transport layer, wherein the evaporation rate ratio of PbI2 and CsBr is 14:1;

[0090] After FAI, FABr, MABr, MACl are mixed in the proportion of 60:7.5:7.2:8, cation solution is obtained by dissolving in ethanol, and the doctor blade coating method is used to coat on lead skeleton layer;Then annealing at 150 DEG C for 15 min to obtain perovskite layer;

[0091] 0.5nm thick lithium fluoride passivation layer is metal evaporated on perovskite layer;

[0092] C 60 And molybdenum disulfide are ball milled for 12h to form a mixture of the two, and then a 20nm thick electron transport layer is prepared by metal evaporation method, C 60 Distributed in the edge area of any two-dimensional structure;

[0093] 15nm thick tin dioxide buffer layer is prepared on electron transport layer by atomic layer deposition method;

[0094] A layer of indium zinc oxide transparent conductive layer with a thickness of about 70nm is prepared on the buffer layer by magnetron sputtering;

[0095] Lithium fluoride anti-reflection layer with a thickness of about 90nm is deposited on the transparent conductive layer by using metal evaporation equipment;

[0096] Silver first electrode is prepared on transparent conductive layer by vacuum evaporation, and silver second electrode is prepared on the back light surface of bottom cell by vacuum evaporation, wherein the first electrode is positive electrode, and the second electrode is negative electrode.

[0097] Example two:

[0098] The difference between this embodiment and example one is that the mass ratio of the transition metal sulfide and C 60 is 10:1.

[0099] Example three:

[0100] The difference between this embodiment and example one is that the mass ratio of the transition metal sulfide and C 60 is 1:10.

[0101] Example four:

[0102] The difference between this embodiment and example one is that the transition metal sulfide is titanium disulfide.

[0103] Example five:

[0104] The difference between this embodiment and example one is that the transition metal sulfide is tungsten disulfide.

[0105] Example six:

[0106] The preparation method of the single-junction solar cell provided in this embodiment comprises:

[0107] Providing a transparent conductive substrate;

[0108] Forming a hole transport layer on the substrate: depositing a 20nm-thick nickel oxide hole transport layer by physical vapor deposition, and preparing a 2-PACz hole transport layer by thermal evaporation;

[0109] Forming a perovskite layer and an electron transport layer on the first transport layer in sequence:

[0110] Preparation of a lead skeleton layer with a thickness of 450nm on the hole transport layer by multi-source co-evaporation, wherein the evaporation rate ratio of PbI2 and CsBr is 14:1;

[0111] Mixing FAI, FABr, MABr and MACl in a proportion of 60:7.5:7.2:8, dissolving them in ethanol to obtain a cation solution, and coating the lead skeleton layer by using a doctor blade coating method; then annealing at 150℃ for 15min to obtain a perovskite layer;

[0112] Ball-milling C 60 and molybdenum disulfide with a mass ratio of 1:1 for 12h to form a mixture of the two, and then preparing a 20nm-thick electron transport layer by metal evaporation, wherein C 60 is distributed in the edge area of any two-dimensional structure;

[0113] A silver first electrode is prepared by vacuum evaporation on the electron transport layer, and a silver second electrode is prepared by vacuum evaporation on the transparent conductive substrate, wherein the first electrode is a positive electrode and the second electrode is a negative electrode.

[0114] Comparative Example 1

[0115] The difference between the present comparative example and Example 1 is that the mass ratio of the transition metal sulfide and C 60 in the present comparative example is 13:1.

[0116] Comparative Example 2

[0117] The difference between the present comparative example and Example 1 is that the mass ratio of the transition metal sulfide and C 60 in the present comparative example is 1:13.

[0118] Comparative Example 3

[0119] The difference between the present comparative example and Example 1 is that the electron transport layer of the present comparative example comprises a molybdenum disulfide layer disposed close to the perovskite layer, and a C 60 layer disposed on the molybdenum disulfide layer.

[0120] Comparative Example 4

[0121] The difference between the present comparative example and Example 1 is that the transition metal sulfide and C 60 in the present comparative example are directly mixed without ball milling during preparation, so that the mixture prepared does not comprise a van der Waals heterostructure.

[0122] Test Data 1

[0123] The solar cells prepared in Examples 1 to 7 and Comparative Examples 1 to 4 are subjected to the following relevant tests:

[0124] The solar cell provided in the present application is subjected to performance tests in terms of open circuit voltage, short circuit current and fill factor using a halm test sorting device, which is a device for simulating sunlight, and is further equipped with an electronic load, a data acquisition and calculation device, etc., for testing the electrical performance of a photovoltaic device (including the performance of a solar cell, such as Eta, Voc, Jsc, FF, etc., which are parameters for reflecting the performance of a solar cell). The silicon wafer of the solar cell subjected to the test is 1.07 cm 2 , the calibrated light intensity is 1000±50 W / m 2 , and the experimental test results are as follows, wherein Voc represents open circuit voltage, Jsc represents short circuit current density, FF represents fill factor, and Eta represents photoelectric conversion efficiency. The experimental test results are shown in Table 1.

[0125] Table 1 Performance test results of solar cells

[0126]

[0127]

[0128] From the data of Examples 1-3 and Comparative Examples 1 and 2, it can be seen that the performance of the examples is better than that of the comparative examples, because the mass ratio of the transition metal sulfide and C 60 in the examples is within the range of 1:10-10:1 of the present application, which is more conducive to regulating the chemical environment of the electron transport layer, and is conducive to the dissociation of the transition metal sulfide, and the formation of a higher content of van der Waals heterostructure in the mixture of the transition metal sulfide and C 60 , which promotes the transition metal sulfide to form more active sites, avoids the recombination of electrons and holes, improves the migration ability of carriers, and helps to change the energy band structure and the position of the Fermi level of the electron transport layer, thereby improving the electrical stability of the electron transport layer and the photoelectric conversion efficiency of the solar cell.

[0129] From the data of Examples 1-5 and Comparative Example 3, it can be seen that the performance of the examples is better than that of Comparative Example 3, because the electron transport layer of the examples is a single layer structure, and the mixture of the layer structure includes a transition metal sulfide and C 60 forms a van der Waals heterostructure, while Comparative Example 3 is a two-layer structure independent of each other, so the number of layers of the examples is less, the interface defects are smaller, and the performance of the electron transport layer is improved to a higher degree due to the presence of the van der Waals heterostructure, thereby improving the photoelectric conversion performance of the solar cell.

[0130] From the data of Examples 1-5 and Comparative Example 4, it can be seen that the performance of the examples is better than that of Comparative Example 4, because the electron transport layer of the examples contains a van der Waals heterostructure, so the van der Waals heterostructure not only helps to improve the carrier transport efficiency of the electron transport layer, but also helps to improve its stability, thereby improving the performance of the solar cell.

[0131] From the data of Examples 1, 4 and 5, it can be seen that the transition metal sulfides of the above examples are molybdenum disulfide, titanium disulfide and tungsten disulfide, respectively, which can all form a van der Waals heterostructure with C 60 , thereby effectively improving the performance of the solar cell, and when molybdenum disulfide is used as the transition metal sulfide, it is more conducive to the formation of a van der Waals heterostructure in the electron transport layer, thereby improving the photoelectric conversion efficiency of the solar cell to a higher degree.

[0132] The above electronic transport layer and the preparation method, the solar cell and the photovoltaic module disclosed by the embodiments of the present application are described in detail, and the principles and implementation manners of the present application are described by applying specific examples. The above embodiment description is only used to help understand the positive electron transport layer and the preparation method, the solar cell and the photovoltaic module. Meanwhile, for those skilled in the art, according to the idea of the present application, the specific implementation manners and application ranges will be changed, and the above description should not be understood as a limitation of the present application.

Claims

1. An electron transport layer for a perovskite solar cell, characterized in that, The electron transport layer comprises transition metal sulfides and C in a mass ratio of 10:1 to 1:

10. 60 And some or all of the transition metal sulfides and the C 60 The mixture is a van der Waals heterostructure, wherein the transition metal sulfide is a stacked two-dimensional layered structure.

2. The electron transport layer of claim 1, wherein, In the electron transport layer, the edge region of any one of the two-dimensional layered structures is distributed with the C 60 .

3. The electron transport layer of claim 1, wherein, The C 60 The particle size of the C is 0.5 nm to 0.9 nm, and the distance between the two adjacent two-dimensional layered structures is 0.0276 nm to 0.3676 nm.

4. The electron transport layer of claim 1, wherein, In the electron transport layer, the size of the transition metal sulfide is 40 nm to 100 nm; and / or, In the electron transport layer, the thickness of the transition metal sulfide is 3 nm to 27 nm.

5. The electron transport layer of claim 1, wherein, The band gap of the electron transport layer is 1.2 eV to 1.9 eV.

6. The electron transport layer of claim 1, wherein, The transition metal sulfide includes at least one of molybdenum disulfide, tungsten disulfide, and titanium disulfide; and / or, The thickness of the electron transport layer is 10 nm to 30 nm.

7. A method of producing an electron transport layer as claimed in any one of claims 1 to 6, characterized in that, The preparation method of the electron transport layer includes the following steps: The C 60 The electron transport layer is prepared after mixing the transition metal sulfide at a mass ratio of 10:1 to 1:

10. 8.The method of claim 7, wherein the electron transport layer is prepared by a method comprising: depositing a first layer on a substrate; and depositing a second layer on the first layer. The C 60 The mixing method with the transition metal sulfide includes a ball milling method or an ultrasonic method; and / or, The C 60 The mixing time with the transition metal sulfide is 12 to 16 hours.

9. A solar cell, characterized by The solar cell includes a substrate, and a first transport layer, a perovskite layer, and a second transport layer arranged on the substrate in sequence, one of the first transport layer and the second transport layer is the electron transport layer according to any one of claims 1 to 6, and the other is a hole transport layer.

10. The solar cell according to claim 9, characterized in that, The substrate includes a bottom cell and an electron-hole recombination layer arranged on the bottom cell, and the first transport layer is arranged on a side of the electron-hole recombination layer away from the bottom cell; The solar cell further includes a transparent conductive layer arranged on a side of the second transport layer away from the perovskite layer, and the solar cell further includes a first electrode and a second electrode, the first electrode is arranged on a side of the transparent conductive layer away from the perovskite layer, and the second electrode is arranged on a side of the bottom cell away from the electron-hole recombination layer, one of the first electrode and the second electrode is a positive electrode, and the other is a negative electrode; Alternatively, the substrate is a transparent conductive substrate, and the first transport layer is arranged on the transparent conductive substrate; The solar cell further includes a first electrode and a second electrode, the first electrode is arranged on a side of the second transport layer away from the perovskite layer, and the second electrode is arranged on a side of the transparent conductive substrate away from the first transport layer, one of the first electrode and the second electrode is a positive electrode, and the other is a negative electrode.

11. A photovoltaic module, characterized by The photovoltaic module includes the electron transport layer according to any one of claims 1 to 6, or the solar cell according to any one of claims 9 to 10.